PENGARUH PRODUK, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN MIE RATE “RAJA TEGA” BALONGPANGGANG GRESIK - Fahmi Fahrizal Pradianto; Hendrik Rizqiawan (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This research aims to analyze the effect of product, price and location on purchase decision. The sample of this research is the people who consume the product of Mie Rate